Microbiome Analyses Demonstrate Specific Communities Within Five Shark Species - Storo, Rachael; Easson, Cole; Shivji, Mahmood; Lopez, Jose V. (Frontiers in Microbiology, 2021)
Profiles of symbiotic microbial communities (“microbiomes”) can provide insight into the natural history and ecology of their hosts. Using high throughput DNA sequencing of the 16S rRNA V4 region, microbiomes of five shark species in South Florida (nurse, lemon, sandbar, Caribbean reef, and tiger) have been characterized for the first time. The microbiomes show species specific microbiome richness, distinct from surrounding seawater. Shark anatomical location (gills, teeth, skin, cloaca) affected the diversity of microbiomes. An in-depth analysis of teeth communities revealed species specific microbial communities. Lemon shark teeth communities (n=11) contained a high abundance of both Vibrio (10.8% ± 26.0%) and Corynebacterium (1.6% ± 5.1%), genera that include human pathogenic taxa. The Vibrio (2.8% ± 6.34%) and Kordia (3.1% ± 6.0%) genera and Salmonella enterica (2.6% ± 6.4%) were the most abundant members of nurse shark teeth microbial communities. The Vibrio genus is highly represented in the sandbar shark (54.0% ± 46.0%) and tiger shark (5.8% ±12.3%) teeth microbiomes. The prevalence of genera containing human pathogens could be informative in shark bite treatment protocol development. We conclude that South Florida sharks host species specific microbiomes that are distinct from their surrounding environment and vary due to differences in microbial community richness among shark species and diversity among anatomical locations.